2011
DOI: 10.1186/1742-9994-8-26
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of blood parasites in seabirds - a review

Abstract: IntroductionWhile blood parasites are common in many birds in the wild, some groups seem to be much less affected. Seabirds, in particular, have often been reported free from blood parasites, even in the presence of potential vectors.ResultsFrom a literature review of hemosporidian prevalence in seabirds, we collated a dataset of 60 species, in which at least 15 individuals had been examined. These data were included in phylogenetically controlled statistical analyses of hemosporidian prevalence in relation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 99 publications
4
88
0
Order By: Relevance
“…A relatively recent review, focusing on avian haemoparasites, concluded that infections 220 probably affect around one third (27 %) of seabirds (Quillfeldt, et al, 2011). In the present study 221…”
Section: Discussion 219supporting
confidence: 48%
“…A relatively recent review, focusing on avian haemoparasites, concluded that infections 220 probably affect around one third (27 %) of seabirds (Quillfeldt, et al, 2011). In the present study 221…”
Section: Discussion 219supporting
confidence: 48%
“…data, Jones and Shellam 1999a), nor from colonies elsewhere in Australia and New Zealand (Quillfeldt et al 2011). However, the distribution, density, biology, physiology and transmission rates of vectors are influenced by changes in climate and habitat (Harvell et al 2002, Rogers & Randolph 2006.…”
Section: Pcr Results and Sequence Analysismentioning
confidence: 99%
“…In addition to this normal large scale movement, the geographic range of many bird species is also affected by changes in climate. In Western Australia, tropical birds have moved into areas that once were the domain of temperate birds (Dunlop & Wooller 1986, Wooller et al 1991, and haemosporidian parasites have been reported in a greater number of species of tropical compared to temperate seabirds (Quillfeldt et al 2011). The expansion of tropical seabirds onto temperate islands such as Penguin Island could therefore result in the introduction or rise in prevalence of such parasites in endemic species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During our 2-year study, including handling over 1000 birds, we saw no apparently sick birds. Avian blood parasites of the genus that causes avian malaria (Plasmodium) are present in Galápagos (Levin et al 2009(Levin et al , 2013, though to date only Haemoproteus parasites have been identified in Sulids and none in Blue-footed Boobies (Quillfeldt et al 2011). Blue-footed Boobies are known to have some parasites, including two endoparasites, a nematode (Contracecum sp.)…”
Section: Discussionmentioning
confidence: 99%